Peran Faktor – Faktor Penentu Minat Beli Konsumen Parfum HMNS - I Kadek Pande Putra Aditya; Putu Purnama Dewi (YUME : Journal of Management, 2025)
This study aims to examine the effect of product quality and price on consumer purchase intention of HMNS perfume on TikTok Shop, with influencer marketing as a mediating variable. The rapid growth of TikTok Shop as a content-based e-commerce platform has intensified competition among local perfume brands, particularly in building consumer trust in products that cannot be physically tested. This research adopts a quantitative approach using a survey method involving 140 respondents who have purchased HMNS perfume through TikTok Shop. Purposive sampling was applied with criteria including Indonesian consumers aged 17 years and above who had prior purchase experience. Data were analyzed using SmartPLS, covering validity, reliability, and structural model testing. The results indicate that product quality and price have a positive and significant effect on purchase intention. Furthermore, both variables significantly influence influencer marketing. Influencer marketing plays a significant mediating role in the relationship between product quality and price on purchase intention. These findings are supported by the Theory of Planned Behavior, which emphasizes attitudes, subjective norms, and perceived behavioral control as key determinants of purchasing intentions. This study provides practical implications for local perfume brands in formulating effective digital marketing strategies by integrating product quality, competitive pricing, and influencer collaboration to enhance consumer purchase intention on digital commerce platforms.Keywords: product quality, price, influencer marketing, purchase intention, TikTok ShopPenelitian ini bertujuan untuk menganalisis pengaruh kualitas produk dan harga terhadap minat beli konsumen parfum HMNS di TikTok Shop dengan influencer marketing sebagai variabel mediasi. Perkembangan TikTok Shop sebagai platform e-commerce berbasis konten mendorong persaingan ketat antar merek parfum lokal, khususnya dalam membangun kepercayaan konsumen terhadap produk yang tidak dapat diuji secara langsung. Studi ini menggunakan metode kuantitatif dengan melakukan survei terhadap 140 orang yang merupakan pelanggan parfum HMNS di toko TikTok. Teknik pengambilan sampel menggunakan purposive sampling dengan kriteria responden berusia minimal 17 tahun dan pernah melakukan pembelian produk HMNS. Analisis data dilakukan menggunakan SmartPLS dengan pengujian validitas, reliabilitas, serta model struktural. Hasil penelitian menunjukkan bahwa kualitas produk dan harga berpengaruh positif dan signifikan terhadap minat beli konsumen. Selain itu, kualitas produk dan harga juga terbukti berpengaruh positif terhadap influencer marketing. Influencer marketing memiliki peran mediasi yang signifikan dalam hubungan antara kualitas produk dan harga terhadap minat beli konsumen. Temuan ini didukung oleh Theory of Planned Behavior yang menekankan peran sikap, norma subjektif, dan persepsi kontrol perilaku dalam membentuk niat pembelian. Penelitian ini memberikan implikasi strategis bagi pelaku usaha parfum lokal dalam mengoptimalkan kualitas produk, strategi harga, dan kolaborasi dengan influencer untuk meningkatkan minat beli konsumen di platform digital.Kata kunci: kualitas produk, harga, influencer marketing, minat beli, TikTok Shop